Exploring gender stereotypes and norms among peri-urban very young adolescents in Zimbabwe using participatory and qualitative approaches. - Owen Nyamwanza; Tariro S Bikwayi; Tariro Chinozvina; Leviticus Makoni; Farai Muronzi; Maxwell Changombe; Angela Obasi; Talent Makoni; Sinokuthemba Xaba; Owen Mugurungi; James R Hargreaves; Frances M Cowan; et al. (PLOS Global Public Health)
Gender stereotypes and norms shape very young adolescents' (VYAs, 10-14 years old) behaviours, including in relation to sexual and reproductive health (SRH). This formative study sought to determine and prioritise the stereotypes and norms to be targeted as part of work to co-develop a gender-transformative intervention for VYAs in Zimbabwe to promote positive masculinities and SRH. In 2023, we collected data from VYAs, using participatory workshops encompassing various activities. We also held focus group discussions with older adolescents and parents/guardians, and individual interviews with community influencers. We used interpretive thematic analysis to generate themes across data. We later presented research findings to diverse stakeholders to explore how the findings might influence the design of our gender-transformative intervention. Gender stereotypes emerged in relation to sexual behaviour and SRH norms. Both boys and girls seemed to condone boys' multiple, concurrent relationships. Boys were deemed to be unable to control their sexual urges. Menstrual stigma, myths and misconceptions were pervasive. Stereotypes were also evident in beliefs and norms around resource and task allocation. For example, both boys and girls concurred that given limited resources, educating a boy child should be prioritised even when a girl sibling is performing better academically. Stereotypes relating to labour distribution were also evident. Daily activity charts suggested longer working hours for girls. Differential attitudes towards drug and substance use among boys and girls were driven by underlying masculine norms. Of note, adolescents disapproved of some of these norms, pointing to an opportunity to shift them. Stakeholders highlighted the need for our planned intervention to focus on the wider community, in addition to VYAs themselves. The formative research enabled us to identify key gender stereotypes and norms, information which is critical for informing the planned gender-transformative intervention. Although deeply seated, these stereotypes are not insurmountable, particularly among VYAs.